MENINGKATKAN KEMAMPUAN LITERASI NUMERASI SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN PBL BERBASIS STEM - Gus Lisna Wati; Ely Syafitri (JURNAL MATHEMATIC PAEDAGOGIC, 2022)
AbstractThe purposeof this study was to determine the improvement of students numeracy literacy skills through a Problem Based Learning (PBL) learning model based on the Science, Technology, Engineering and Mathematics (STEM) approach. This type of research is classroom action research which consists of 2 cycles, with 4 stages,namely planning, implementation, observation and reflection. The instrument used is an observation sheet on the implementation of learning and literacy test. The results of this study indicate that the numeracy literacy skills of students with high and moderate mathematical abilities in general can complete, where students can : (1) work effectively with models in concrete but complex situations, (2) represent different information and relate it to real situations. Analyze numeracy skills in this study the students were grouped. Keywords: Numerical Literacy; Problem Based Learning (PBL) Based On Science,  Technology, Engineering, and Mathematics (STEM) Approach; Phytagorean Theorem;